IGF-1, BDNF, and NGF mediate the neuro-modulatory role of stem cells in acrylamide-induced hippocampal toxic changes in rats - Nabila Youssef Abdel Halim; Gamal Hosny Mohamed; Ahmed Elhusseiny; Marwa Abdelgwad; Reda Abdelnasser Imam (Folia Morphologica)
BACKGROUND: Acrylamide (ACR), a common industrial chemical, is a strong neurotoxic material. The hippocampus is a brain area of interest often affected by Alzheimer’s disease (AD). The usefulness of mesenchymal stem cells (MSCs) in various neurological diseases including AD is unclear. We aimed to explore the role of MSCs in ACR-induced hippocampal neurodegeneration and elucidate the mediating mechanism. MATERIALS AND METHODS: For this purpose, 10 rats served as controls, another 10 were injected with ACR (i.p. 50 mg/kg/day for 2 weeks), and the last 10 rats were injected with ACR in addition to MSCs (i.p. 1 × 107 MSCs single injection). RESULTS: ACR induced neurodegenerative histopathological hippocampal changes and adversely altered the hippocampal oxidative stress markers SOD, MDA, and GSH. ACR induced hippocampal demyelination as detected by silver staining. ACR significantly (p < 0.05) up-regulated the ELISA hippocampal TNF-α (tumour necrosis factor alpha) and interleukin-6 (IL-6) and produced microglial and astrocyte activation (as tracked by Iba1 and GFAP immunohistochemistry respectively). ACR significantly reduced hippocampal PCR gene expression of IGF-1 (insulin growth factor-1), BDNF (brain-derived neurotrophic factor), and NGF (nerve growth factor). However, MSCs administration mitigated all these deleterious changes. CONCLUSIONS: Acrylamide causes detrimental effects on the hippocampus and demonstrably alters the hippocampal architecture. Bone marrow mesenchymal stem cells offer a promising therapeutic role against the neurotoxic effects of acrylamide, presumably through modulation of IGF-1, BDNF, and NGF gene expressions.